2021
DOI: 10.1080/23322039.2021.1938379
|View full text |Cite
|
Sign up to set email alerts
|

Audit partner rotation, and its impact on audit quality: Evidence from India

Abstract: Using multiple indicators of audit quality, the study examines the impact of audit partner rotation on audit quality in India based on 1,694 firm years for the period of 2011-2017 when the institutional set up for audit partner rotation was voluntary. The empirical results indicate that the audit partner rotation had no significant impact on audit quality as measured by discretionary accruals and going concern audit opinion. The study finds that other factors like loss year, size of the firm, value, leverage h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…Similarly, Salehi et al (2022) reported that mandatory audit firm rotation did not influence EM estimated under the real activity manipulation (RAM) approach rather than increased discretionary accruals based EM. Furthermore, these findings are consistent with those of Mohapatra et al (2021), who found that auditor switching has no significant impact on audit quality.…”
Section: Additional Control Of Auditor Rotationsupporting
confidence: 90%
See 1 more Smart Citation
“…Similarly, Salehi et al (2022) reported that mandatory audit firm rotation did not influence EM estimated under the real activity manipulation (RAM) approach rather than increased discretionary accruals based EM. Furthermore, these findings are consistent with those of Mohapatra et al (2021), who found that auditor switching has no significant impact on audit quality.…”
Section: Additional Control Of Auditor Rotationsupporting
confidence: 90%
“…The role of audit firm tenure. According to the "Knowledge Spillover Hypothesis", the audit firm's tenure enables audit partners to get more experience, knowledge and familiarity with clients businesses, which enables them to improve audit quality (Mohapatra et al, 2021). Similarly, the longer tenure of an audit partner yields better auditor quality as compared to shorter tenure, and this is due to the loss of knowledge after the auditor switches off (Daugherty et al, 2013).…”
Section: 42mentioning
confidence: 99%
“…With regards to the size of the auditee firms and audit quality, the extant literature finds size of the firm to have a positive influence on audit quality, with large and profitable companies having superior expertise in financial accounting activity and financial resources available for its organizations over small companies (Carp and Istrate, 2021) [4]. Mohapatra et al (2021) document that the larger the size of the firm, higher the audit quality. Similarly, firms with good financial performance (ROA) would be signalling to investors regarding the better state of the firms’ current or future prospects, and one could speculate a positive or negative impact on audit quality.…”
Section: Methodsmentioning
confidence: 99%
“…In India, studies before the MAR enactment also show that a long auditor tenure enhanced audit quality (Jadiyappa et al, 2021). Even after the introduction of MAR, empirical evidence with respect to auditor partner rotation was found to be negative on audit quality (Mohapatra et al, 2021). While the evidence is mixed, overall, it shows that MAR does not increase audit quality.…”
Section: Mandatorymentioning
confidence: 99%
“…As per our knowledge, studies have not been done using a JA attribute for the Indian context; the present study attempts to fill this research gap. The second, auditor tenure, has been studied in international studies (Ghosh and Moon, 2005; Gul et al ., 2009; Lim and Tan, 2009; Manry et al ., 2008) but cannot be accepted in Indian legal and economic structures further recent studies conducted in the Indian context by (Jadiyappa et al ., 2021; Mohapatra et al ., 2021) used DA an inverse proxy for audit quality (AQ). Auditor tenure is negatively related to AQ (Jadiyappa et al ., 2021), whereas (Mohapatra et al ., 2021) found that auditor rotation does not impact AQ.…”
Section: Introductionmentioning
confidence: 99%